Methodology of Literary Criticism Based on the Theory of Feminism - Bilal Ahmad Fazli (Randwick International of Education and Linguistics Science Journal, 2023)
Feminism is an organized movement to defend women's rights, whose roots go back to the Periods of European Enlightenment (Renaissance). Throughout its long history, this movement wanted to overthrow the patriarchal system and eliminate the rule of gender discrimination. Feminism officially began its activity at the end of the 18th century and has gone through a period full of ups and downs since then. The three important waves of this movement are considered to be one of its most important activities, whose basic goals are "preserving the right to vote for women, and emphasizing protest against gender, social and economic differences and inequalities." After the feminism movement, feminist criticism emerged followed the reflection of women's voices and their experiences in literature and started its activities from the second half of the 20th century. The works of famous writers such as “Virginia Woolf” and “Simon de Boir” are eminent examples of this movement. In this article, we have reviewed the methods that can be used to study literary works from the perspective of feminist criticism, as well as the things that a literary critic can do to write a good and interesting critique of a work based on the theory of feminism. The result showcased that Critics who take a feminist approach in criticizing literary texts do not deny the existence of differences between male and female characters in the works. It may be said that the view that women are different from men basically corresponds to patriarchal ideology, but it must be said that the third wave feminists do not deny the existence of a difference between men and women, and in their opinion, the difference between women and men can even be seen in the readiness or potential ability of women to establish interpersonal communication and recognize it as a symbol of compassion, empathy and kindness. In addition, we have also stated that it can be a good guide in the field of writing feminist criticism on literary and artistic works.